Effect of diabetes mellitus on prognosis and development of hepatocellular carcinoma in patients with hepatitis C-related cirrhosis (Annals of Medical Research, 2021)
Aim: Hepatitis C virus (HCV) infection and diabetes mellitus (DM) negatively affect each other. HCV patients diagnosed with DM have more complications than patients with HCV infection alone. In this study, we aimed to investigate the effect of DM on complication rate, hepatocellular cancer (HCC) development and mortality in HCV RNA (+) cirrhosis patients.Material and Methods: Patients admitted with Hepatitis C-related cirrhosis and followed up for at İzmir Katip Çelebi University Atatürk Training and Research Hospital Gastroenterology and Internal Medicine Clinic for at least six months between 2005and 2014 were retrospectively evaluated.Results: A total of 146 patients with HCV-related cirrhosis were included in the study. Of these patients, 53 (36.3%) had diagnosis of DM. In 108 patients who did not develop hepatocellular carcinoma (HCC), the mean CHILD score at final admission (p=0.024), difference between mean CHILD scores at final and initial admission (p=0.011), and annual rate of increase in CHILD score (p=0.047) was significantly higher in the DM group. There was no significant difference between the DM and non-DM groups according to both overall survival (p=0.115) and time of HCC development (p=0.567).Conclusion: While HCC development and overall survival were similar in both groups, in the subgroup of patients who did not develop HCC, the annual increase in CHILD score and final CHILD score were significantly higher in DM patients.
Keywords: Diabetes mellitus; HCV; cirrhosis; survival; hepatocellular carcinoma.